2015
DOI: 10.1002/jhm.2313
|View full text |Cite
|
Sign up to set email alerts
|

Bedside diagnosis of dysphagia: A systematic review

Abstract: Background Dysphagia is associated with aspiration, pneumonia and malnutrition, but remains challenging to identify at the bedside. A variety of exam protocols and maneuvers are commonly used, but the efficacy of these maneuvers is highly variable. Methods We conducted a comprehensive search of seven databases, including MEDLINE, EMBASE and Scopus, from each database’s earliest inception through June 5th, 2013. Studies reporting diagnostic performance of a bedside examination maneuver compared to a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 74 publications
(477 reference statements)
0
92
1
2
Order By: Relevance
“…We expect this work will help to guide physiologically based therapeutic exercises aimed at prolonging swallowing function in this population. Additionally, kinematic assessment of bulbar function during the swallow may help identify critical markers of bulbar decline, which will improve the management of risks associated with dysphagia [38, 39] and improve timing of the implementation of diet modifications and non-oral feedings [38, 39]. …”
Section: Limitations and Future Workmentioning
confidence: 99%
“…We expect this work will help to guide physiologically based therapeutic exercises aimed at prolonging swallowing function in this population. Additionally, kinematic assessment of bulbar function during the swallow may help identify critical markers of bulbar decline, which will improve the management of risks associated with dysphagia [38, 39] and improve timing of the implementation of diet modifications and non-oral feedings [38, 39]. …”
Section: Limitations and Future Workmentioning
confidence: 99%
“…14,[17][18][19][20]71,74,75 This review focuses on a single method, the WST, and controlled for the heterogeneity in the literature using appropriate statistical analyses. Despite these methods, the variability of our results is similar to previous reviews, strongly suggesting that robust statistical methods cannot correct for limitations in experimental methods.…”
mentioning
confidence: 99%
“…During the hospital stay, the team begin the specialized care, in order to encourage deinstitutionalization and avoid or minimize potential complications of stroke (6) . The speech-language therapy in these cases can help reduce hospital costs (21) . The results of this study showed that there was progress in the integration of the speech-language therapist in the public hospital services in Paraiba, between 2010 and 2014, as the total number of speech-language therapists associated to these sites almost doubled during the study period.…”
Section: Discussionmentioning
confidence: 99%